Specialized Education in Enhancing Life Satisfaction Among Caregivers of Children with Autism - Manisha Thakur; Anita Chauhan (International Journal of Children, 2024)
Autism spectrum disorder (ASD) is a complex neurodevelopmental condition that significantly impairs a person's ability to communicate, engage in social interactions, and exhibit typical behavioral patterns. Raising a child with autism presents several difficulties for couples. Specialized education can be beneficial for children with autism. The study aims to identify the role of special education and satisfaction rates among autistic caregivers. The result shows that special education causes a 37.9 % change in caregiver stress. The requirement for more care and support is what makes autism a special need. These particular demands are supported and their potential is fully realized with the aid of specialized teaching approaches. Specialized teaching strategies, tailored lesson plans, and encouraging learning settings are all used in special education programs to meet the special requirements of kids with autism. These programs not only improve the educational results for kids with autism, but they also offer a disciplined environment that can lessen stress and worry in caregivers. In conclusion, because it necessitates more care and support, autism is seen as a special need. In order to meet their specific demands and enable them to reach their greatest potential, specialized education approaches have been developed. The comparatively low degree of hope and life satisfaction among parents of autistic children highlights the need for special education resources to be developed further and made more easily accessible in order to enhance the quality of life for both the children and their families. Enhancing support networks and doing continuous research are necessary to provide a more welcoming and encouraging learning environment for kids with autism.
Keywords: Autism spectrum disorder (ASD); Quality of life; autism; caregiver; life satisfaction; parenting; special education